Target the Ego or Target the Group: Evidence from a Randomized Experiment in Proactive Churn Management - Godinho de Matos, Miguel; Pedro, Ferreira; Rodrigo, Belo (Marketing Science, 2018)
We propose a new strategy for proactive churn management that actively uses social network information to retain consumers.